Essential epidemiology : an introduction for students and health professionals - Webb, Penny, 1963-; Bain, Chris, 1947-; Page, Andrew, 1974- (Cambridge, United Kingdom : Cambridge University Press, 2020)
Authored by experienced epidemiologists and academics, this book introduces concepts logically and builds knowledge from chapter to chapter. Now in its fourth edition, Essential Epidemiology is an engaging and accessible introduction to the foundations of epidemiology. It addresses the study of infectious and chronic diseases, public health and clinical epidemiology, and the role of epidemiology in a range of health monitoring and research activities. Contemporary, historical and hypothetical examples enable students to engage with content, while mathematics is kept understandable with complex mathematics housed in optional material so the book remains accessible. With over ninety questions and answers to work through in the print book, and hundreds more in the interactive eBook, this book is an essential resource for students, practitioners and anyone else who needs to interpret health data in their studies or work. Epidemiology's most important goal is to bring rigour to the collection, analysis and interpretation of health data to improve health on a global scale; Essential Epidemiology provides readers the tools to achieve that goal.
Epidemiology is ... -- How long is a piece of string? : measuring disease frequency -- Who, what, where and when? : descriptive epidemiology -- Healthy research : study designs for public health -- Why? : linking exposure and disease -- Heads or tails? : the role of chance -- All that glitters is not gold : the problem of error -- Muddied waters : the challenge of confounding -- Reading between the lines : reading and writing epidemiological papers -- Who sank the boat? : association and causation -- Assembling the building blocks : reviews and their uses -- Surveillance : collecting health-related data for epidemiological intelligence and public health action / Martyn Kirk, Penelope Webb and Chris Bain -- Outbreaks, epidemics, and clusters / Martyn Kirk, Adrian Sleigh and Penelope Webb -- Prevention : better than cure? -- Early detection : what benefits at what cost? -- Epidemiology and the public's health.
Includes bibliographical references and index.
Keywords: Epidemiologic methods; Epidemiology